METAFORA KONSEPTUAL PENYAKIT DALAM MAJALAHMEDIAKOM: SUATU KAJIAN SEMANTIK KOGNITIF - Ilham Munandar; Tajudin Nur (Kantor Bahasa Provinsi Maluku Utara, 2020)
The use of metaphors in daily life can be found in the mass media, such as magazine. Mediakom is a magazine which published by Indonesian Ministry of Health, focuses on the health of Indonesian people. The use of conceptual metaphors of disease has found in Mediakom magazine, and it is the focus on this research. The research data is collected from Mediakom issue of the June 107, 2019 concerning ‘Preventable Cancer’. The research method is using qualitative descriptive with cognitive semantics approach. Lakoff and Johnson’s theory of conceptual metaphors has used as references to analyze data. The result shows, there are three types of conceptual metaphors found within Mediakom issue of the June 107, 2019 ‘Preventable Cancer’ 1) structural metaphors with concepts of enemy, war, and struggle, as well as with an image schema of the force, 2) orientational metaphors with concepts of anger, achievement, growth, experience, and effort, as well as with image schemas of the space and scale, and 3) ontological metaphors with concepts of explosion, expansion, disappointed, and journey, as well as with image schemas of the existence and identity.